PENGGUNAAN MEDIA DIGITAL WORDWALL DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Najma Soraya; Hutri Hidayah; Noor hafizah; Nova Soraya; Wahdah Refia Rafianti; Ahmad Suriansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Indonesian language learning in elementary schools requires the use of interactive media that can increase student engagement, motivation, and understanding of the material. However, learning at SDN Banua Anyar 10 is still dominated by conventional methods, resulting in students being less active, losing focus easily, and not fully understanding the material. This study aims to describe the use of Wordwall digital media in Indonesian language learning, specifically hyperbole material in third grade, and its impact on student motivation, focus, and understanding. This study uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The results showed that the use of Wordwall significantly increased student engagement, making the learning atmosphere more interactive and enjoyable. Students' understanding of the material also improved, as indicated by their ability to identify examples of hyperbole more accurately. In addition, Wordwall helped students maintain their focus on learning longer than conventional learning. Teachers also experienced an increase in their skills in using digital media, despite initial technical obstacles. Thus, Wordwall is effective as a medium for teaching Indonesian language in elementary schools and has the potential to be applied to other subjects and levels.